Criminal Policy on Countering Organized Crime Against Land Ownership in the Perspective of Criminal Law Reform - Darmawan, Yuda Pratama; Suetani, Lies; Pujiwati, Yani (JUSTISI, 2025)
This research aims to analyze the countermeasures of organized criminal acts related to land ownership in Indonesia and analyze criminal policies to overcome these criminal acts in the future from the perspective of criminal law reform. The method used is a normative juridical method, which examines library materials and secondary data related to legislation and literature relevant to the problem under study. The novelty of this research lies in the clarity of the function of the Land Mafia Task Force attached to each institution, which aims to avoid sectoral ego. The results show that the settlement of land mafia cases is carried out using penal and non-penal approaches. The penal settlement serves as a catalyst for strict law enforcement, while the non-penal approach focuses on preventive efforts. Although countermeasures against organized crime have been implemented by involving Law Enforcement Officials and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency through the Anti Land Mafia Task Force, this organized crime is still challenging to solve because it is carried out in a structured and organized manner. The conclusion of this research is that legal reform is needed to tackle this problem, which has the potential to cause huge losses and many victims. The suggested legal reform is to prioritize non-penal policies that are sustainable through cooperation between relevant stakeholders. Thus, overcoming organized crime against land ownership can be done thoroughly, starting from prevention through public education and prosecution of perpetrators to recovery of losses for victims and closing the space for new, more varied crimes.